Enhancement on selenium volatilization for phytoremediation: role of plant and soil microbe interaction - Karna, Ranju R.; Kumara, Samantha T.; McCracken, Vance J.; Fowler, Thomas J.; Lin, Zhi-Qing (Frontiers in Plant Science, 2024)
This study aimed at quantifying the potential effects of plant and soil microbial interaction on selenium (Se) volatilization, with the specific objectives of identifying soil bacteria associated with rabbitfoot grass (Polypogon monspeliensis) and demonstrating the enhancement of Se volatilization in the soil-Indian mustard (Brassica juncea) system through inoculation of the soil with the identified best Se-volatilizing bacterial strain. Soil bacteria were isolated from topsoil and rhizosphere soils of rabbitfoot grass, and the bacterial colonies were characterized via PCR-DGGE and DGGE band analysis prior to their identification using 16S rDNA sequencing technique. Bacillus cereus produced over 500-fold more volatile Se in a culture medium treated with 15 µg Se/mL (equal mixture of SeO42-, SeO32- and selenomethionine) than any of the other eight identified bacterial strains. Inoculation of Indian mustard vegetated soil with the best Se volatilizing bacterial strain B. cereus resulted in a significant (p<0.05) increase in Se volatilization during a 7-day time period, compared to the soil-plant system without inoculation of B. cereus. Thus, inoculation of the soil with B. cereus substantially enhanced Se removal via biogenic volatilization in the soil-Indian mustard system. This study evaluated the role of B. cereus in enhancing Se volatilization in soil-plant systems, and demonstrated the importance of plant and soil microbial interaction for Se phytoremediation.